Is timber management a realistic conservation alternative for indigenous Amazonian communities? - Fitts, Lucia Alejandra; Cruz-Burga, Zoila Aurora; Legatzke, Hannah; La Torre-Cuadros, María de los Ángeles (Ethnobiology and Conservation, 2022)
Indigenous people, who are often economically, socially, and culturally dependent on forests, represent important stakeholders in forest management. Due to high costs, indigenous communities partner with external institutions to harvest timber, often resulting in forest degradation within their territories, internal and external conflicts, and disinterest in starting new timber management projects. Using a standardized methodology to investigate the outcomes of previous community forestry projects presents an opportunity to better understand and potentially resolve further issues. To investigate this issue, we conducted research in the Sinchi Roca I native community in Peru. Our objectives were: (1) to describe the process of timber harvest; (2) to analyze gender differences in local perception of timber management; and (3) to evaluate the outcomes of the timber activity, applying socioeconomic criteria and indicators. Data collection included in-depth interviews, focus group discussions, and intra-household surveys. We found that locals partnered with a company for timber harvesting, which led to a sanction from the Peruvian government. Timber harvesting was negatively perceived in the community, with 83.75% of survey respondents dissatisfied with the activity and 88.75% reporting internal and external conflicts due to the presence of the company. Moreover, women did not have a major role in timber harvesting, nor did they actively participate in planning meetings. Results suggest that improving future timber management projects in indigenous communities requires that projects be adapted to local realities and encourage local participation, including training for locals in governance, administration of documents, and negotiations with external stakeholders.